Nonmigrating tidal impact on the CO2 15 μm infrared cooling of the lower thermosphere during solar minimum conditions. Issue 6 (16th June 2017) - Nischal, N.; Oberheide, J.; Mlynczak, M. G.; Hunt, L. A.; Maute, A.
Abstract: Carbon dioxide (CO2 ) infrared emissions at 15 μm is the primary radiative cooling mechanism of the thermosphere in the altitude range of 100–135 km. This paper explores the role of two important diurnal nonmigrating tides, the DE2 and DE3, in the modulation of CO2 15 μm emissions during the solar minimum year 2008 by (i) analyzing Sounding the Atmosphere using Broadband Emission Radiometry (SABER) CO2 cooling rate data and (ii) photochemical modeling using dynamical tides from the empirical Climatological Tidal Model of the Thermosphere model. Tidal diagnostics of SABER data shows that the CO2 cooling rate amplitudes for the DE2 and DE3 components are on the order of approximately 20–50% relative to the monthly means, and they maximize around the lower bound (100 km) of the analyzed height interval. The photochemical modeling reproduces the observed results, albeit with systematic amplitude differences which is likely related to the uncertainty in the model input backgrounds, especially atomic oxygen. The main tidal coupling mechanism is found to be the temperature dependence of the collisional excitation of the CO2 ν 2 vibrational state. However, neutral density becomes equally important above ∼110 km, thereby explaining observed evanescent DE2 and DE3 phases which are not present in temperature tides. The contribution of vertical tidal advection is comparatively small. The relative importance of the coupling mechanisms is the same at all latitudes/seasons. These results indicate that upward propagating nonmigrating tides forced by latent heat release in the lower atmosphere impact the thermospheric energy budget by modulating the longitudinal/local time behavior of the CO2 infrared cooling. Key Points: DE2 and DE3 tides from the lower thermosphere modulate the 15 μm CO2 cooling rates in the lower thermosphere by up to 50% Large‐scale weather systems impose large longitude/local time variations on the energy budget of the lower thermosphere Main tidal driver below 110 km is temperature but neutral density equally important above 100 km